In-situ X-ray observations of ultrasound-induced explosive decomposition. (June 2019) - Mares, Jesus O.; Roberts, Zane A.; Emre Gunduz, I.; Parab, Niranjan D.; Sun, Tao; Fezzaa, Kamel; Chen, Weinong W.; Son, Steven F.; Rhoads, Jeffrey F.
Graphical abstract: Highlights: Ultrasound is used to study "hot spot" formation and explosive initiation. This work details observations of the heating and decomposition of an explosive. Interfacial friction is shown to be a dominant heating mechanism. Abstract: High-strain mechanical loading of polymer-bonded explosives can produce significant stress concentrations due to microstructural heterogeneities, resulting in localized thermal "hot spots". Ultrasound produces similar effects and has been proposed as a tool to study the thermomechanical interactions related to explosive initiation. Detailed observations of the processes governing the generation of heat in these materials are severely lacking, yet they are vital for identifying salient physics, improving the modeling tools used to predict mechanical response, improving explosives safety, and providing insight into the initiation mechanisms of explosion. Here we report on high-speed, high-resolution in-situ observations, obtained via synchrotron X-ray phase contrast imaging and diffraction, of the heating and decomposition of an explosive material under ultrasonic excitation. We demonstrate that interfacial friction is a dominant heating mechanism and can lead to a violent reaction in the explosive particles. Furthermore, sub-surface particle temperatures are estimated via diffraction.